Pengaruh Persepsi Mahasiswa tentang Program PPG dan Profesi Guru Terhadap Minatnya Menjadi Guru - Janu Pinardi; Abd Rahman Azahari; Bejo Basuki (Jurnal Ilmiah Kanderang Tingang, 2023)
The purpose of this study was to determine the effect of student perceptions of the PPG program and the teaching profession on interest in becoming a teacher in students of mathematics education at the University of Palangka Raya. This research is a causal associative study conducted in the Mathematics Education Study Program, FKIP UPR. The research instrument used was a questionnaire. The classical assumption tests are: normality test with Kolmogorov Smirnov, multicollinearity test with variance inflation factor (VIF) and heteroscedasticity test using scatter plot method. Data analysis used linear regression, namely t test, F test and R-Square (coefficient of determination) with Minitab 16 application. The results showed that; (1) there is a positive and significant effect between the perception of mathematics students about the PPG program and their interest in becoming a teacher, with a regression coefficient of 0.0495 and a value of > (6.50 > 1.99) and p-value = 0.000 <0.05. (2) there is no significant positive effect between student perceptions of the teaching profession on interest in becoming a teacher, with a regression coefficient of 0.0495 and a value of > (1.04 > 1.66) and p-value = 0.299 > 0.05. (3) there is a significant positive effect on the perception of mathematics students towards the PPG program and the teaching profession on interest in becoming a teacher, the value of > (35.62 > 3.09) and p-value = 0.000 <0.05. (4) The R-Square value of 0.404 or 40.4% means that the influence given by the combination of perceptions of mathematics students about the PPG program and the teaching profession on interest in becoming a teacher is 40.4% while the remaining 59.6% is influenced by other variables.